Resurrection of the genus Eumonospora (Apicomplexa: Sarcocystidae) for Caryospora species without Stieda body. (August 2020) - Chou, Shyun; Tokiwa, Toshihiro; Hadano, Shinichiro; Izawa, Nobumoto; Ueda, Michihiro; Kojima, Atsushi; Ike, Kazunori
Abstract: The coccidian genus Eumonospora Allen, 1933 is re-established. Despite morphological features and host preference among species, coccidian with octasporozoic and monosporocystic oocysts are traditionally consider to belonging in the genus Caryospora Léger, 1904 (Apicomplexa: Eimeriidae). Recently, the genus Avispora Schuster et al., 2016 was proposed for above caryosporoids parasitizing birds based on combined morphological and phylogenetic analyses. However, diagnostic morphological characters of the genus Avispora, the absence of Stieda and substieda bodies, has already been mentioned in the description of the genus Eumonospora Allen, 1933 (Apicomplexa: Sarcocystidae), and thus Avispora is considered to be a junior synonym of Eumonospora. In this study, caryosporoid coccidians were detected from five owl species; Bubo scandiacus, Ptilopsis leucotis, Athene noctua, Strix nebulosa, and Pulsatrix perspicillata (Strigiformes: Strigidae) and identified as Avispora henryae (Yakimoff & Matikaschwaili, 1932) described from Bubo bubo (Strigiformes: Strigidae). Eumonospora henryae (Yakimoff & Matikaschwili, 1932) comb. nov. is redescribed for this species based not only on morphological features but also on phylogenetical analyses. The key of the genus Eumonospora and a list to the species known at present are also provided. Graphical abstract: Unlabelled Image Highlights: Monosporocystic oocysts were obtained from 5 owl species. All were identified as Avispora henryae (Yakimoff & Matikaschwaili, 1932). A new combination Eumonospora henryae (Yakimoff & Matikaschwili, 1932) was proposed for the present species. Twenty-five new combinations were also proposed in the genus Eumonospora.